Salivary cortisol response to psychological stress in children with early childhood caries - Kambalimath Halaswamy; Dixit Uma; Thyagi Parimala (Wolters Kluwer Medknow Publications, 2010)
Aims and Objectives: Early Childhood Caries (ECC) is a multi-factorial disease and has numerous biological, psychological, and behavioral risk factors. In this study, we have attempted to study psychological stress as a risk factor for early childhood caries by investigating and comparing the response of event-related stress on salivary cortisol level in children with ECC and those without ECC and also compared the adaptability to various dental procedures in children with early childhood caries and without early childhood caries. Materials and Methods: One hundred children aged between four and five years were examined in the school and 16 pairs of children with caries and without caries were selected after cross-matching them on various risk factors for Early Childhood Caries. Oral prophylaxis and topical fluoride treatment procedures were used as stressors and salivary samples were collected at the time of arrival for the treatment, after Oral Prophylaxis and Fluoride treatment. The salivary samples were analyzed by radioimmunoassay for an unbound plasma cortisol level. Results: Statistical analysis was performed using a paired t-test, on the collected data, to compare the mean values of the salivary cortisol across the group and within the groups to evaluate the cortisol response to stress. No significant differences were found between the salivary cortisol levels prior to treatment, post oral prophylaxis, or post fluoride treatment at the first and second appointments of both groups. At the first appointment, the fluoride treatment caused a significant increase in the salivary cortisol level over the pretreatment level, in both the groups, but it was not evident in either of the two groups studied at the second appointment. Conclusion: We have concluded that the stress produced by different dental procedures was similar in children from the two groups studied, and the coping ability of the children was also similar in both the groups. Small sample size may be one of the reasons why no significant differences were found between the groups. Similar study needs to be repeated with a larger sample size.